2021
DOI: 10.3390/s21062014
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Devices and Sensors for Remote Care of Heart Failure Patients

Abstract: The large and growing burden of chronic heart failure (CHF) on healthcare systems and economies is mainly caused by a high hospital admission rate for acute decompensated heart failure (HF). Several remote monitoring techniques have been developed for early detection of worsening disease, potentially limiting the number of hospitalizations. Over the last years, the scope has been shifting towards the relatively novel invasive sensors capable of measuring intracardiac filling pressures, because it is believed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Radhoe et al . 30 conducted a review of invasive remote haemodynamic sensors that monitor haemodynamic changes in HF patients and showed that CardioMEMS was the most effective device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radhoe et al . 30 conducted a review of invasive remote haemodynamic sensors that monitor haemodynamic changes in HF patients and showed that CardioMEMS was the most effective device.…”
Section: Discussionmentioning
confidence: 99%
“…Although CardioMEMS 9 was recently approved for guided treatment in HF patients and has been shown to be effective in reducing readmissions in HF patients 9 as well as a cost-effective monitoring method, 9,28,29 we did not include this in our review as CardioMEMS is an invasive technique, not broadly applicable to the majority of frail, elderly patients. Radhoe et al 30 conducted a review of invasive remote haemodynamic sensors that monitor haemodynamic changes in HF patients and showed that CardioMEMS was the most effective device.…”
Section: Interventionsmentioning
confidence: 99%
“…Many non-COVID patients may benefit from remote monitoring and management as well, in particular cancer patients treated by chemotherapy, patients discharged from hospital after a major surgery, and patients with chronic disease at high risk of hospital re-admission. In patients with congestive heart failure, the remote monitoring of pulmonary artery pressure with an implantable micro-electromechanical system (aka MEMS) has been shown to be useful to adjust therapy and prevent hospital readmissions [ 12 ]. Whether similar benefits could be reported with non-invasive bioimpedance necklaces able to detect early changes in thoracic fluid content remains to be determined [ 13 ].…”
Section: Home Monitoringmentioning
confidence: 99%
“…Finally, we can still remember the great importance of ways of remote monitoring of patients, especially at times like the one we faced during the Covid-19 pandemic. (3)…”
Section: Comment On: Safety and Feasibility Of Hemodynamic Pulmonary Artery Pressure Monitoring Using The Cardiomems Device In Lvad Managmentioning
confidence: 99%